Storytelling as a Medium of Patriarchy Critique: A Narrative Analysis of Women's Subordination, Silencing, and Objectification in Nyai Gowok - Agustina, Hiqma Nur; Sakinah, Yanik Lailinas (Journal of Language and Literature Studies, 2026)
This study examines the storytelling elements in the novel Nyai Gowok through narrative analysis, focusing on how the narrative portrays women as victims of patriarchy. The novel is significant because it depicts women’s lives in a traditional Javanese setting where gender roles are shaped by unequal power relations. Although previous studies have explored the novel’s cultural and historical aspects, few have analyzed how storytelling techniques convey women’s oppression. This study addresses that gap by examining how narrative elements function as a medium of patriarchy critique. The research analyzes plot, characterization, setting, point of view, and symbolic motifs to understand how gender roles and power relations are constructed and maintained. Using storytelling theory and patriarchy as the main analytical framework, the study explores how conflict development, characterization patterns, and symbolism shape the reader’s perception of the female protagonist. The findings show that the protagonist is portrayed as an object of desire, a silenced voice, and a subordinate figure whose identity is largely defined by male authority and social expectations. Nyai Gowok’s experiences reflect the normalization of unequal power relations and the internalization of patriarchy values. However, the narrative also presents subtle forms of resistance that challenge dominant gender norms. Data were collected through close reading of the text. This study contributes to gender and literary studies by showing how narrative structure and symbolism reveal persistence of patriarchy and possibility of resistance in culturally rooted literary texts.